Theoretical analysis of the power generation of pumping cycle kite power systems compared to traditional wind turbines in Aberdeen - Ye, Zhihui; Chaer, Issa; Hartungi, Rusdy; Ross, Marcus (Frontiers in Built Environment, 2023)
The UK has pledged to reduce its greenhouse-gas emissions to net zero by 2050. However, in July 2022, the High Court ruled that the government's net zero strategy failed to outline policies that would enable it to meet the target. As a result, the government published a new plan that sets out opportunities for innovative technologies like Floating Offshore Wind Manufacturing, and hydrogen, which will not only help us reach net zero. For wind, the government goal is to develop up to 50GW of offshore wind by 2030. The challenge of such an expansion is huge. It means the UK will need to install an estimated 3,200 new, and much larger, wind turbines by 2030roughly three new turbines every two days. Airborne wind turbine is an innovative design alternative for wind turbines that can benefiting from the higher velocity and persistence of wind at high altitudes while avoiding the expense of tower construction, or the need for slip rings or yaw mechanisms. Scotland is the most suitable location for the implementation of Airborne Wind Energy (AWE) systems in the UK. In this feasibility study, the characteristics of wind energy distributions were theoretically investigated by developing a wind speed distribution model, then the annual power production of a kite system and a turbine system with a 30 kW generator were analysed by applying the annual wind profile in Aberdeen to the performance models of these two systems. It was found that the annual power production of the kite system was two times higher than that of a normal turbine system.